Innovative strategy of agricultural industry development of the Republic of Kazakhstan - Tolysbayev, B.S.; Suslov, V.I.; Moldakenova Е.К. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the formation postindustrial technological paradigm in the context of the global innovative technological space in the first half of the XXI century. The paradigm determined modern national economic policy of the Republic of Kazakhstan, which is aimed at achieving sustainable development of the country via a dynamic diversification of industries and refusal raw material model of development. Production of competitive and export-oriented goods and services in agriculture and service sector is the main goal of governmental industrial and innovation policy. Consequently, one of the main aims of providing innovative development of agriculture is to create favorable conditions for the formation of the innovation fund and development in the production process by smoothing existing differences between the results obtained in production and the potential of scientific and technological projects. This refers to both an available and affordable to consumers quantitative set of innovations and their ability to improve the productive, economic and other indicators of agricultural industry.